Networks of Participation and Influence: Attitudes and Behaviors of a “High Threshold” Person Living with HIV-AIDS - Brian Bantugan; Pricila Marzan; John Mark Distor (East Asian Journal of Multidisciplinary Research, 2023)
This study looked into the networks of participation and influence (NPI) of a person living with HIV-AIDS to unfold the ways by which attitudes and behaviors after diagnosis are potentially influenced by them. Using a single case study approach and qualitative research design, an anonymized interview transcript was used for document analysis as it featured a person living with HIV-AIDS (PLHIV) who is unbothered by his HIV-positive diagnosis. Narratives were broken down into smaller units that highlighted relationships that played a crucial role in his experiences as he coped with the knowledge of his diagnosis and thereafter. Through thematic analysis, the study found that building a network of a variety of health-related professionals dealing with HIV-AIDS helps a PLHIV deal better with his HIV-positive diagnosis.  Findings suggest that creating a culture where empathic and ethical health professionals dealing with stigmatized illnesses due to HIV can become part of a primary network of support for populations vulnerable to HIV. Creating a NPI may be key to alleviating anxieties that result from HIV infection.